Analyzing the Functions of Rab11-Effector Proteins During Cell Division - Prekeris, Rytis (Methods Cell Biol, 2015)
Recycling endosomes recently have emerged as major regulators of cytokinesis and abscission steps of cell division. Rab11-endosomes in particular were shown to transport proteins to the mitotic ingression furrow and play a key role in establishing the abscission site. Rab11 GTPase function by binding and activations various effector proteins, such as Rab11 family interacting proteins (FIPs). FIPs appear to be at the core of many Rab11 functions, with FIP3 playing a role in targeting of the Rab11-endosomes during mitosis. Here we summarize the newest finding regarding the roles and regulation of FIP3 and Rab11 complex, as well as describe the methods developed to analyze membrane and cytoskeleton dynamics during abscission step of cytokinesis.